Effect of dietary peNDF levels on digestibility and rumen fermentation, and microbial community in growing goats - Zhou, Jia; Xue, Benchu; Hu, Anhai; Yue, Shuangming; Wu, Mei; Hong, Qionghua; Wu, Yuhan; Wang, Zhisheng; Wang, Lizhi; Peng, Quanhui; Xue, Bai (Frontiers in Microbiology, 2022)
Physically effective neutral detergent fiber (peNDF) is a concept that account for the particle length of NDF in diets, sustaining the normal chewing behavior and rumen fermentation of ru-minants. Specifically, peNDF>1.18 is the commonest one that is calculated from NDF and the percentage of feed dry matter left on the 1.18 mm, 8.00 mm and 19.00 mm sieves. This study aimed to investigate the effects of different levels of peNDF>1.18 on rumen microbiome and its correlation with the nutrient digestibility and rumen fermentation in goats. A total of 30 Lezhi black goats were randomized blocked to five dietary treatments (n =6). All the diets were identical in composition but varied in hay lengths, leading to the different peNDF>1.18 content of the diets: 32.97%, 29.93%, 28.14%, 26.48%, and 24.75%. The results revealed that the nutrient digestibility increased when dietary peNDF>1.18 levels decreased from 32.97% to 28.14%, with the highest digestibility at 28.14% peNDF>1.18 treatment, after which nutrient digestibility decreased with the decreasing of dietary peNDF levels. Ruminal NH3-N concentration in the 29.93% and 28.14% groups were higher than that in the 24.75% group (p < 0.05). Ruminal microbial protein concentration was the highest in the 32.97% group (p < 0.05). Daily CH4 production in the 32.97% and 24.75% peNDF>1.18 treatments were lower than that in the 26.48% group (p < 0.05) and no differences were observed among other groups. The relative abundance of rumen fungi at the phylum and genus levels and archaea at the species were affected by dietary peNDF>1.18 content. In conclusion, decreasing dietary peNDF>1.18 levels within a certain range can improve nutrient digestibility and change the rumen microbial community structure of goats. Dietary peNDF>1.18 level should be 28.14% (roughage length around 1 cm) among the five levels for 4 months Lezhi black goats with the purpose of optimal nutrient digestibility.